A coupled connector element for nonlinear static pushover analysis of precast concrete diaphragms. (1st March 2015) - Wan, Ge; Zhang, Dichuan; Fleischman, Robert B.; Naito, Clay J.
Highlights: Precast diaphragm connector elements are developed for use in nonlinear FE model. Connector element construction based on full-scale diaphragm connector test data. Connector elements coupled for shear–tension interaction and friction mechanisms. Elements show good agreement with tests and capture important diaphragm behavior. Abstract: This paper describes the formulation of a diaphragm connector element developed for use in two-dimensional finite element (2D-FE) modeling of precast concrete diaphragms. The connector elements, composed of assemblages of standard element types readily available in most FE software package libraries, are nonlinear, coupled for shear–tension interaction, enable friction mechanisms, and possess descending branch behavior. Element construction is based on data from full-scale tests of common precast diaphragm connectors. The 2D-FE models have been employed in nonlinear static "pushover" analysis of isolated floor diaphragms to determine diaphragm stiffness, strength, deformation capacity, and limit state sequence. The use of discrete elements to model the precast diaphragm connectors permits the direct evaluation of local force and deformation demands acting on these details. Further, the coupled formulation is adaptable to complex force histories and deformation patterns in the floor diaphragm, thereby permitting the element to respond in realistic fashion. The models, verified for accuracy using large scale testing, are providing crucial information on capacity and limit states for calibrating performance-based design factors for a new seismic design methodology for precast concrete diaphragms.